Efficacy of Cetylpyridinium Chloride Used as Oropharyngeal Antiseptic - Pitten, Frank-Albert; Kramer, Axel (Arzneimittelforschung, 2001)
Cetylpyridinium chloride, (CPC, CAS 123-03-5) as active ingredient of antiseptic oral mouthrinses has a broad antimicrobial spectrum with a rapid bactericidal effect on gram-positive pathogens and a fungicide effect on yeasts in particular. There are gaps in its effectiveness against gram-negative pathogens and mycobacteria.Application of CPC at a concentration of 0.05 % as a mouthrinse results in an immediate reduction in bacterial counts of 2.0 to 2.5 log steps (which is adequate to > 99 %). This reverts to about 1 log step (= 90 %) 1 h after application.The ability of CPC to inhibit plaque and thereby reduce gingivitis is assured. In comparison to chlorhexidine, CPC has a lower residual effect, and as a result a lesser effect against plaque and gingivitis. The efficacy of CPC against oropharyngeal candidiasis is assured. CPC mouthrinses can significantly reduce infectious aerosols in dental practice, thereby protecting both staff and the patient. The balance of intra-oral bacterial flora is not disturbed even in the case of relatively long-term use of CPC (up to six weeks).Taking these properties into consideration, CPC may be considered as an alternative active ingredient in the case of chlorhexidine intolerance in the treatment and prevention of bacterial or fungal disorders of the oropharyngeal cavity. It is also of interest as an element for combination in the development of new types of oropharyngeal antiseptics.
Keywords: Antiseptic, oropharyngeal; CAS 123-03-5; Cetylpyridinium chloride, antimicrobial efficacy; Plaque